Foveal hypoplasia in a patient with achromatopsia - Aydın, Rukiye; Yalçın Özbek, Merve; Karaman Erdur, Sevil; Şentürk, Fevzi (Masson Editeur, 2018)
[Abstract Not Available]
WOS: 000434461500010
PubMed ID: 29773314
Keywords: Color Vision Defects; Cyclic Nucleotide-Gated Cation Channels; Nucleotide-Gated CNG; Pathologyretina; Foveavisual; Disorder